Lanthanide-based hybrid nanostructures: Classification, synthesis, optical properties, and multifunctional applications - Singh, Priyam; Kachhap, Santosh; Singh, Prabhakar; Singh, S.K. (Coordination chemistry reviews, 2022)
•Introductory aspect and overview of the lanthanide-based hybrid materials.•Classification of the components of the hybrid nanostructure.•Types of interactions between/among different phases in the hybrid nanostructure.•Energy transfer processes and multi-modal emission.•Multifunctionality of the lanthanide-based hybrids. Lanthanide-based hybrid materials have impacted numerous areas of research and development namely for bio-imaging: optical imaging, magnetic resonance imaging, and tomography, sensors: optical, thermal, and gas sensors, optical switches, and detectors, anti-counterfeiting, energy harvesting, etc. The list of their applications is still increasing and immense efforts are in progress. Unexpectedly, the last extensive review on the subject appeared more than a decade ago. While a lot of progress has been made since then with the evolution of some entirely new aspects as well. This makes it vital to outline the recent developments and to look for the future prospective. The present review starts with an introductory aspect and an overview of the components of lanthanide-based hybrid materials. Further, it covers fundamental facets of the hybrid material design with particular reference to inorganic phosphors, organic β-diketonate complexes, organic dyes, metal-organic frameworks, semiconductor quantum dots, halide perovskite quantum dots/nanocrystals, plasmonic NPs, graphene quantum dots, etc. The synthesis techniques, surface chemistry, and physical structure of different types of hybrids have discoursed in detail. In the next step, their optical properties, both upconversion, and downshifting-based emission have been unraveled. The integration of different types of QDs and plasmonic nanoparticles (AgNPs and AuNPs) with the hybrid materials affects the optical properties significantly and introduces additional functionality to them. Finally, different state-of-the-art applications of hybrid nanostructures, as listed above, have been summarized at length. In the final remarks, the review discusses the remaining challenges and future opportunities in this field of research.